Participatory Design of Waste Bank Management for Residents of RT 09 RW IX Sendangmulyo Semarang: Perancangan Desain Partisipatif Pengelolaan Bank Sampah Warga RT 09 RW IX Kelurahan Sendang Mulyo Semarang - Rizka Arinta; Pascal Galih Sadana (Universitas Lancang Kuning, 2023)
Independent waste management has become a mandatory program for several areas in Semarang City. For the residents of RT IX RW IX, Sendang Mulyo Village, Semarang, this program has been implemented since 2020. The high enthusiasm of the residents made this activity require a container that can accommodate waste bank activities, from the collection, sorting, and weighing to transportation. This need triggered the architect's role in designing the waste bank area. Design sustainability requires architects to create valuable designs, so the participatory design method was chosen as the waste bank design method. The implementation process is carried out with four main stages, the first is observation and interviews, the second is making alternative designs, the third is public discussion and dissemination to the community, and the fourth is finalizing the design. The results of designing this waste bank design so that it has social value involves two main things: the space requirements of users (community and managers) and design efficiency in terms of dimensions and selection of facade materials. In future waste bank designs, you can explore both of these things.